Two new Cu(ii) and La(iii) 2D coordination polymers, synthesis and in situ structural analysis by X-ray diffraction. Issue 32 (29th July 2016) - Lundvall, F.; Wragg, D. S.; Dietzel, P. D. C.; Fjellvåg, H.
Abstract : Two new coordination polymers, CPO-71-Cu and CPO-72-La, were synthesized by solvothermal methods using 4, 4′-dimethoxy-3, 3′-biphenyldicarboxylic acid as the organic linker. The two-dimensional frameworks of both CPO-71-Cu and CPO-72-La exhibit thesql topology. Abstract : Two new coordination polymers were synthesized solvothermally using 4, 4′-dimethoxy-3, 3′-biphenyldicarboxylic acid (H2 dmbpdc), and di- and trivalent metal salts (Cu(NO3 )2 ·2.5H2 O and La(NO3 )3 ·6H2 O). Their structures were determined by single-crystal X-ray diffraction analysis, and their thermal stability was evaluated by thermogravimetric analysis. The copper compound Cu(dmbpdc)(DMF; N, N -dimethylformamide), CPO-71-Cu, is based on the well known copper acetate paddlewheel secondary building unit. The asymmetric unit comprises one copper cation with one DMF molecule and one linker molecule coordinated. The lanthanum compound La2 (dmbpdc)3 (DMF)(H2 O)3, CPO-72-La, is formed from a dimer of nine-coordinate, edge sharing lanthanum cations. To this dimer, three water molecules and one DMF molecule are coordinated in an ordered fashion. In addition, the asymmetric unit contains three crystallographically unique linker molecules. Both CPO-71-Cu and CPO-72-La form two-dimensional layered structures, and topological analyses revealsql topologies with point symbol 4 4 ·6 2 and vertex symbol 4·4·4·4·6(2)·6(2). The thermal behavior of CPO-71-Cu was investigated in an in situ structural analysis by variable temperature powder- and single-crystal X-ray diffraction.